Prevalence and intention to use HIV counseling and testing service among Thai youth - Kulrawee Wiwattanacheewin (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The aims of this cross-sectional, mixed method design study were to explore the prevalence of sexual experienced youth, use and intention to use an HIV counseling and testing (HCT) service, predictors of HCT service used among sexually experienced youth, and the youth friendly HCT (YFHCT) service expected by youth. There were 2,945 participants from 6 secondary and 3 vocational schools in Bangkok invited to complete web-based questionnaires at the schools' computer labs. Of those, 2,536 questionnaires were completed and analyzed by using descriptive statistics and Logistic Regression Analysis. Telephone interviewing with 20 youth volunteers and content analysis was used in these qualitative sessions. There were 783 youth who reported they had ever had a sexual experience (prevalence=30.88%); only 143 of them had ever been tested for HIV (prevalence= 18.26%). Among those who never used HCT services (n=640), 474 intend to use them in the future (Prevalence= 70%). Use of HCT service was influenced by HIV knowledge (OR=3.105, p< .05), attitude toward HIV testing (OR=1.029, p< .005), actual risk for HIV by having one sex partner and using a condom consistently (OR=2.356, p< .05) and having multiple sex partners and using condom inconsistently (OR=1.961, p< .05), and being informed about HCT service and knowing where HCT is located (OR= 4.373, p< .001). Unconditional intention was influenced by expectations for YFHCT services (OR =1.020, p =001), attitude toward HIV testing (OR=1.038, p<.001), perceived high risk (OR =2.452, p =.023), having multiple sex partners and using condoms consistently (OR=3.714, p<.05), willingness to pay for service (OR=3.453, p<.001), and knowing about HCT service and its location (OR =2.348, p<.001). Conditional intention to use HCT service was predicted by expectations for YFHCT services (OR =1.018, p<.001), perceived low risk for HIV infection (OR =1.892, p=.025), and willingness to pay (OR=2.959, p<.001). The characteristics of YFHCT services expected by youths were the following: 1) HCT service locations should not be in hospitals and should be private with a good atmosphere; 2) Youth-friendly HCT services should be provided with accessible, unlimited, convenient times and provided for free; and 3) friendly providers should be of the same gender with understanding, confidentiality and no judgment. Scaling up HCT services used by sexually experienced youth is one of major challenges to solve the HIV/AIDS epidemic in Thailand. A YFHCT service should be provided to meet this challenge.